2018
DOI: 10.1016/j.ebiom.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Midkine Controls Arteriogenesis by Regulating the Bioavailability of Vascular Endothelial Growth Factor A and the Expression of Nitric Oxide Synthase 1 and 3

Abstract: Midkine is a pleiotropic factor, which is involved in angiogenesis. However, its mode of action in this process is still ill defined. The function of midkine in arteriogenesis, the growth of natural bypasses from pre-existing collateral arteries, compensating for the loss of an occluded artery has never been investigated. Arteriogenesis is an inflammatory process, which relies on the proliferation of endothelial cells and smooth muscle cells. We show that midkine deficiency strikingly interferes with the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 52 publications
4
55
0
Order By: Relevance
“…Midkine (MK), a heparin-binding growth factor that seems to play an important role in arteriogenesis by mediating eNOS activity and increasing the bioavailability of VEGFA [164], has also been related with GH, as the expression of MK and its receptors have been detected in somatotrophs of both embryonic and adult rats, favoring the development of the pituitary gland and acting as a regulator of its function in adults [165]. MK seems to be secreted by follicle-stimulating cells in the pituitary gland, controlling GH production from GH cells in a paracrine way via protein tyrosine phosphatase receptor-type Z (Ptprz1) [166].…”
Section: Gh and Midkine (Mdk) Relation Should Be Investigatedmentioning
confidence: 99%
“…Midkine (MK), a heparin-binding growth factor that seems to play an important role in arteriogenesis by mediating eNOS activity and increasing the bioavailability of VEGFA [164], has also been related with GH, as the expression of MK and its receptors have been detected in somatotrophs of both embryonic and adult rats, favoring the development of the pituitary gland and acting as a regulator of its function in adults [165]. MK seems to be secreted by follicle-stimulating cells in the pituitary gland, controlling GH production from GH cells in a paracrine way via protein tyrosine phosphatase receptor-type Z (Ptprz1) [166].…”
Section: Gh and Midkine (Mdk) Relation Should Be Investigatedmentioning
confidence: 99%
“…It has been shown that MDK is positively associated with angiogenesis while inversely associated with osteogenesis 43,44 , potentially via MAPK and PI3K signaling 45 . High expression of CD105 has been shown to disrupt angiogenesis in tumor tissue, and CD105 -BM-MSCs are more prone to differentiate into adipocytes and osteocytes 11,46 .…”
Section: Osteoblast Precursor Induce Angiogenesis During Coupling Witmentioning
confidence: 99%
“…VEGF is a glycoprotein produced by a variety of cell types including leukocytes such as neutrophils or monocytes [22][23][24][25] and is critically involved in enhancing endothelial cell proliferation, permeability, and angiogenesis [26][27][28]. The role of VEGF in arteriogenesis remained uncertain for a long time; however, it has now been established that its downstream signaling events are crucial for this process [3,25].…”
Section: Erna Initiates Arteriogenesis By Locally Enhancing Vegf/vegfmentioning
confidence: 99%
“…VEGF is a glycoprotein produced by a variety of cell types including leukocytes such as neutrophils or monocytes [22][23][24][25] and is critically involved in enhancing endothelial cell proliferation, permeability, and angiogenesis [26][27][28]. The role of VEGF in arteriogenesis remained uncertain for a long time; however, it has now been established that its downstream signaling events are crucial for this process [3,25]. While it has been demonstrated that the expression of the isoform VEGF-A is not increased in collateral vessels during the process of arteriogenesis and that administration of additional VEGF does not significantly improve collateral vessel development [16,29], antibodies blocking either VEGF or the cognate receptor (VEGFR2) have been shown to interfere greatly with vessel remodeling [25,30,31].…”
Section: Erna Initiates Arteriogenesis By Locally Enhancing Vegf/vegfmentioning
confidence: 99%